2018
DOI: 10.1002/naaq.10059
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Kaolin Clay on Aeromonas hydrophila Growth, Chemotaxis, and Virulence to Channel Catfish

Abstract: Aeromonas hydrophila is one of the most widespread bacterial pathogens affecting freshwater fish, and an emerging pathotype of A. hydrophila has severely impacted the catfish industry over the last decade. In this study, we evaluated the effect of treatment with kaolin (Al2Si2O5[OH]4), an inert clay, on A. hydrophila chemotaxis and adhesion (two important steps of the infective process) to catfish mucus and the potential use of kaolin for controlling A. hydrophila outbreaks. Chemotaxis assays revealed that kao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…They concluded that kaolin could reduce gill pathologies and bacterial attachment to key tissues and increase survival in Channel Catfish exposed to F. covae . Kaolin has also been proven to be effective in blocking chemotaxis and adherence of Aeromonas hydrophila in the mucus of Channel Catfish [ 39 ]. Kaolin treatment at a rate of 0.1% increased survival ( p < 0.05) compared to control (untreated) Channel Catfish in the same study [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that kaolin could reduce gill pathologies and bacterial attachment to key tissues and increase survival in Channel Catfish exposed to F. covae . Kaolin has also been proven to be effective in blocking chemotaxis and adherence of Aeromonas hydrophila in the mucus of Channel Catfish [ 39 ]. Kaolin treatment at a rate of 0.1% increased survival ( p < 0.05) compared to control (untreated) Channel Catfish in the same study [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kaolin has also been proven to be effective in blocking chemotaxis and adherence of Aeromonas hydrophila in the mucus of Channel Catfish [ 39 ]. Kaolin treatment at a rate of 0.1% increased survival ( p < 0.05) compared to control (untreated) Channel Catfish in the same study [ 39 ].…”
Section: Introductionmentioning
confidence: 99%